2013
DOI: 10.1179/1351000213y.0000000040
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte caspase-3 and antioxidant defense is activated in red blood cells and plasma of type 2 diabetes patients at first clinical onset

Abstract: Increased antioxidant defense in plasma and RBCs of early type 2 diabetes patients is a potential mechanism that can overcome oxidative damage induced by reactive oxygen species overproduction, and occurs even in RBCs with a decreased life span. This observation could provide a possible explanation for the controversial effects of antioxidant supplementation in diabetes patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…An alternative study found DM patients to have higher PS exposure due to the suppression of flippase enzyme activity, the suppression of which was caused by higher levels of membrane tubulin [ 109 ]. RBC cell death in T2D patients was also documented and associated to be with increased RBC caspase 3 activation [ 110 , 111 ].…”
Section: Multifactorial Mechanisms Explaining Shortened Rbc Lifespan ...mentioning
confidence: 99%
“…An alternative study found DM patients to have higher PS exposure due to the suppression of flippase enzyme activity, the suppression of which was caused by higher levels of membrane tubulin [ 109 ]. RBC cell death in T2D patients was also documented and associated to be with increased RBC caspase 3 activation [ 110 , 111 ].…”
Section: Multifactorial Mechanisms Explaining Shortened Rbc Lifespan ...mentioning
confidence: 99%
“…Diabetes has been known to stimulate apoptosis by the activation of caspase-3 in affected tissues (Savu et al, 2013 ). Using an animal model of T2DM, Kim et al in their studies demonstrated an increased level of tau phosphorylation and cleavage in the brains of db/db mice which are models for diabetic dyslipidemia (Kim B. et al, 2013 ).…”
Section: Crosstalk Of T2dm and Tau Pathology In Admentioning
confidence: 99%
“…Kumar et al [68] also found increased plasma SOD activity in patients with RA, similarly to Mazzetti et al [69]. Similar results were found in early type 2 diabetes patients [70], where increased antioxidant defense in plasma and erythrocytes is explained as a potential mechanism that can overcome oxidative damage induced by ROS overproduction. There are some reports on erythrocyte SOD, CAT, and GPx activities in patients with RA or in rats with AA, but the results are controversial [71,72].…”
Section: Evaluation Of Results Of Administration Of Hyaluronans In Exmentioning
confidence: 57%